Analysis of the stream function for peristaltic flow of Jeffrey fluid Under The Influence Of Rotation and Electric field in Porous medium - sagban, malath (Iraqi Journal of Science, 2026)
In this paper the effect of electric field and rotation on the peristaltic flow of a fluid in an asymmetric channel with porous medium is studied